A Review on Post Stroke Shoulder Pain Management - Rahman, Md Shahidur (Bangladesh Journal of Neuroscience, 2013)
Shoulder pain is critically important obstacle to functional recovery in most of the stroke sufferers. Hemiplegic shoulder pain causes considerable distress and reduced activity and can markedly hinder rehabilitation. The etiology of hemiplegic shoulder pain is probably multifactorial. The ideal management of hemiplegic stroke pain is prevention. For prophylaxis to be effective, it must begin immediately after the stroke. Awareness of potential injuries to the shoulder joint reduces the frequency of shoulder pain after stroke. The multidisciplinary team, patients, and care givers should be provided with instructions on how to avoid injuries to the affected limb. Shoulder strapping may be used to prevent shoulder pain. Over arm slings should be avoided. Treatment should include analgesics heat or cold therapy, electrical stimulation and pain free exercise as well. This review was done to find the recent developments in post-stroke shoulder pain management by extracting the published articles in this topic. The ultimate objectives were to delineate most rational and effective treatment options for post-stroke shoulder pain. Bangladesh Journal of Neuroscience 2013; Vol. 29 (1) : 54-59